Cofactors and equilibria for polynomial vector fields. Issue 4 (24th July 2014) - Ferragut, Antoni; Llibre, Jaume
Abstract : We present a relationship between the existence of equilibrium points of differential systems and the cofactors of the invariant algebraic curves and the exponential factors of the system.